ARAH DAN TOPIK PENELITIAN DALAM BIDANG AKUNTANSI MANAJEMEN - Nur Indriantoro (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
This paper presents a systematic framework on several recent topics, theories, approaches, and directions in management accounting research Accordingly, this paper examines several literature reviewed by Kaplan (1993), Shields (1997), Foster and Young (1997), and that of Atkinson et.al. (1997). In this regard, topics in management accounting research are ranked as follows (started with the topic being studied most frequently): management control system ranked first, cost accounting ranked second, and cost management ranked third. Apparently, more than half of management accounting studies employ economic-based theories, and the remaining half employ theories from organizational behaviour, psychology, production/operation management, sociology, strategic management, and a combination of the five, in terms of directions four research resources are still of today's trend: (I) extensions from previous literature, (2) new research theories and methodologies introduced by doctoral students, (3) teaching byproducts, and (4) issues in management accounting practice.